Dietary or in ovo Saccharomyces cerevisiae Supplementation Developed Growth, Caecal Microbiota and Gut Histology of Broiler Chicks - Salih Gülen; İsa Coşkun (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the effects of in ovo injection of Saccharomyces cerevisiae (SC) to fertile Ross 308 broiler eggs or dietary supplementation on growth performance, internal organ development, gut histomorphology and cecum microbiota during 14 d of growing period. This study was designed as 2×2 factorial experimental design. Fertile 92 Ross 308 eggs were injected with SC solution 0.2ml at 18d of hatch and 90 eggs non-injected as control, afterward dietary SC supplementation was applied during the 14 d to broiler diet. In this study, 160 broiler chicks were used in four treatment groups at 10 replicate for each treatment group and 4 chicks for each replicates. Treatment groups were A) in ovo SC injection + dietary SC supplementation, B) in ovo SC injection + basal diet, C) no injection + dietary SC supplementation, D) no injection + basal diet as control. Live weight, feed consumption, feed conversion ratio and gut histomorphology, caecum microbiota, internal organ weight were recorded at 14 days of age. Live weight gain increased in C group than in the D group. Feed consumption, feed conversion ratio and internal organ weights were not affected by the treatments. Villi length and villi width increased in A group among the other treatment groups in jejunum, villi length increased in A and C groups among the other groups in ileum. Villi length/villi width ratio increased in A group than in the D group in ileum, was not different in jejunum. LAB counts in caecum were higher in A group than those of C and D groups, but was not different from B group. Enterobactericaea count was lower in A and B group than in the D group, was not different from C group. To conclude, results showed that dietary Saccharomyces cerevisiae supplementation increased broiler growth at 14 day by increasing villi development and improving gut health.